2020
DOI: 10.3390/bios10080080
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Coated Superparamagnetic Nanoflowers for Biosensors Based on Lateral Flow Immunoassays

Abstract: Superparamagnetic iron oxide nanoflowers coated by a black carbon layer (Fe3O4@C) were studied as labels in lateral flow immunoassays. They were synthesized by a one-pot solvothermal route, and they were characterized (size, morphology, chemical composition, and magnetic properties). They consist of several superparamagnetic cores embedded in a carbon coating holding carboxylic groups adequate for bioconjugation. Their multi-core structure is especially efficient for magnetic separation while keeping suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The units provided by this sensor are µΩ·mm coming from the cumulative integral of the impedance (µΩ) across the width of the test line (mm). It has been demonstrated that the impedance change is directly proportional to the number of superparamagnetic nanoparticles at the test line, which enables to determine the analyte concentration [ 38 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The units provided by this sensor are µΩ·mm coming from the cumulative integral of the impedance (µΩ) across the width of the test line (mm). It has been demonstrated that the impedance change is directly proportional to the number of superparamagnetic nanoparticles at the test line, which enables to determine the analyte concentration [ 38 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, magnetic nanoparticles could be a suitable label to both improve detection and achieve quantitative LFIA. Recently, we have developed a quantitative magnetic LFIA for EVs detection [ 38 ]. For this approach, magnetic LFIAs have been coupled to a sensor developed by the authors to get the quantification for different concentration of isolated EVs from human plasma [ 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors have also been widely employed in tissue engineering to modulate cell polarity, to tune the cellular functions, detection of biomolecules, and diagnosis of tissue disease 228 . Recently, various hybrid materials prepared using chitosan, gold NPs, graphene, and IONPs have been utilized to design novel biosensors for glucose detection, 229 ROS detection, 230 catecholamine neurotransmitters in brain tissues, 231 extracellular vesicles detection, 232 cellular detection of hydrogen peroxide, 233 glucose/urea detection, 234 tumor necrosis factor‐α, 235 and multiple immune biomarkers 236 in biological samples.…”
Section: Applicationsmentioning
confidence: 99%
“…The biotin-neutravidin complex is one of the strongest non-covalent interactions that due to the high specificity and strong affinity is widely used in immunoassays [21,22]. In this study, the biotin-neutravidin system was applied as model system in order to study the feasibility of using SPIONs in PLGA-PVA/PC as labels for LFIA.…”
Section: Biotin-neutravidin Affinity Testmentioning
confidence: 99%